Limitations of outcome based accounting curriculum in Ethiopia - Deresse Mersha; Mohammed Getahun (Financial Studies, 2019)
The demand for accounting profession is increasing from time to time because of the increase in complexity of the business environment. Education institutions are responsible to produce qualified and ethical accountant required by the accounting profession. Specifically, Technical and Vocational Education and training (TVET) colleges play great role in training lower and middle level accountant in Ethiopia. However, Academicians, practitioners and employers are raising concern on the quality and relevance of education and training given by TVET colleges. The major objective of this study is to examine the limitations of TVET in accounting curriculum in relation to relevance and contents of the competences included. The finding of the study showed that the existing curriculum has a lot of limitations in terms of relevance, coherence and content. As a result, the existing curriculum should be revisited in order to make it better.
Keywords: M4; 330; Accounting education; Competence based; Curriculum limitations; TVET